EFEKTIVITAS KONSELING KELOMPOK TEKNIK MIRAQLE QUESTION UNTUK MENINGKATKAN SELF EFFICACY SISWA KELAS X 6 SMA NEGERI 1 COLOMADU TAHUN 2025/2026 - Fitri Nur Hidayah; Adi Putro, Eko; Dwi Sholikhah, Linda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Fitri Nur Hidayah THE EFFECTIVENESS OF GROUP COUNSELING USING THE MIRACLE QUESTION TECHNIQUE TO IMPROVE SELF-EFFICACY OF CLASS X 6 STUDENTS AT SMA NEGERI 1 COLOMADU IN THE 2025/2026 ACADEMIC YEAR : The purpose of this study was to determine the effectiveness of group counseling services using the miracle question technique in improving self-efficacy among students of class X 6 at SMA Negeri 1 Colomadu in the 2025/2026 academic year. Self-efficacy is an individual's belief in their own ability to perform a task, face challenges, and achieve certain goals. This research employed an experimental method with a one-group pretest-posttest design. The research subjects were 10 students from class X 6, selected through purposive sampling. The instrument used in this study was a questionnaire to measure students' self-efficacy before and after being given group counseling using the miracle question technique. The data obtained were analyzed using the Wilcoxon test, which showed a significance value of 0.005 < 0.05, thus H0 was rejected and Ha was accepted. The results of this study indicate that there was an increase in students' self-efficacy after participating in group counseling using the miracle question technique. Therefore, it can be concluded that there is a difference in the mean scores before and after the intervention, and that group counseling using the miracle question technique is effective in improving the self-efficacy of class X 6 students at SMA Negeri 1 Colomadu in the 2025/2026 academic year. This study is expected to contribute to the development of guidance and counseling programs in schools in order to foster positive outcomes for students.